Pendampingan Manajemen Dan Kelembagaan Bumdes Bumdes Management And Institution Assistance - Siswadi Sululing; Yanti Mutalib (Karunia: Jurnal Hasil Pengabdian Masyarakat Indonesia, 2023)
This Community Service activity was carried out in Sapelang Village, South Buko District with the topic "BUMDes Management and Institutional Assistance". The purpose of implementing this community service activity is to transfer knowledge and provide solutions to problems faced by Prosperous BUMDes. The implementation method used is mentoring which consists of providing material on BUMDes Management and BUMDes Management accompanied by practice and evaluation. The results of the practice and evaluation of BUMDes management participants have understood, so they know the main tasks and responsibilities of each based on a clear organizational structure and understand making standard operating procedures and BUMDes Management consisting of planning, organizing, implementing and supervising thanks to practice and answering questions correctly.